Pemberdayaan Ekonomi Masyarakat Melalui Pembuatan Deterjen di Gampong Mideun Jok Samalanga Kabupaten Bireuen - Nurbaiti; Asyura, Khairun; Afrizal; Fakrurradhi; Nurvela (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2023)
This community service initiative aims to create a sustainable positive impact on the economic development and empowerment of women in Gampong Mideun Jok, particularly through the production of detergent. The method employed involves providing understanding or socialization, practical application of acquired knowledge, and motivating partners regarding productive economic ventures. This activity yields positive outcomes in enhancing the skills and knowledge of young women and empowering the local community economically. The training on detergent production has successfully increased their capacity in micro-enterprises, providing a sustainable economic alternative. The involvement of the Al-Aziziyah Samalanga Institute of Islamic Studies (IAI) has significantly contributed to the implementation of the project, fostering a positive synergy between higher education institutions and the community. This program encourages economic inclusion and promotes women's participation in local economic development.